GUBERNATORIAL POLICY ON PILGRIMAGE DEVELOPMENT IN BANTEN - Fartini, Ade; Nita Anggraeni; Sendi Wardana (AL-QISTHAS: JURNAL HUKUM DAN POLITIK, 2025)
The Banten Provincial Government has implemented various policies to manage religious tourism. These policies include infrastructure development, tourism promotion, and local community empowerment. In this study, several Banten areas became the focus of research or research places. Among them are: Banten Lama Sultanate Area (KKB), Sultan Maulana Yusuf Worship, and Sultan Ageng Tirtayasa Pilgrimage. This research will discuss the Pergub Policy on the development of the Banten pilgrimage. This research will see how the role of the government in this case the local government coordinates the pilgrimage sites in the Banten region, especially these 3 pilgrimage sites through policies issued by the Governor, Regent / Mayor. Penelitian ini menerapkan metode penelitian hukum empiris. The approach uses Juridical Sociology, where this research is studied about what is behind the emergence of the application of the law. This research uses Primary Data sources, using direct interviews. Using secondary sources of legal information is beneficial in strengthening and expanding the findings of this research. The results of this study The revitalization of the Banten Lama Sultanate Mosque was carried out by the Provincial Government by involving several sectors, such as the PUPR Office, Tourism, Environmental Services, Transportation Services, and other sector lines. The reason for the revitalization of KKB is because the Icon of Banten, namely the Great Mosque of Banten, is located in the Old Banten Sultanate Area (KKB). Panempbahan Sultan Maulana Yusuf Pilgrimage Currently, pilgrimage parties do not involve the role of local government in the management of the tomb. The Sultan Ageng Tirtayasa Pilgrimage is more worrying than the two pilgrimages that the author mentioned above.